Protected Private Information for Proximity Computingin Mobile Social Network - Jinshuang Li; Fengyun Li (Dianxin kexue)
Mobile social network（MSN）extend social network in the cyberspace into the real world.It allows mobile users to discover and interact with a stranger in their physical vicinity.Proximity computing means that two users can compare their personal profiles in MSN application.It is,however,possible disclosing user's privacy information.To address this concerns,two novel proximity computing protocols were designed.The protocols enable two users to perform proximity computing without disclosing any information about their profiles.